Validation of the stroke drivers screening assessment for patients with an acquired neurological disability - Radford, Kathryn A. (2001)
The Stroke Drivers Screening Assessment (SDSA) is a collection of three cognitive tests found predictive of driving in stroke patients. Whilst two of the test (Square Matrices and Road Sign Recognition) were good predictors of on-road performance, it remained unknown whether the SDSA could predict fitness to drive for people with other acquired neurological disabilities. The on-road test, considered the 'gold standard' of driving ability, was the criterion against which SDSA performance was compared. Since the SDSA's validity depends on the reliability of the driving instructor's decision, it seemed important to check that this was consistent with instructors elsewhere. Therefore this study had three aims:- i)To examine the content and concurrent validity of the SDSA sub test. ii)To determine whether the SDSA, either alone or in conjunction with other cognitive tests, could predict fitness to drive for patients with acquired neurological disabilities other than stroke. iii) to check the inter-rater reliability of the gold standard of driving ability (used in studies to validate the SDSA).